210k views
5 votes
What is the difference? x+5/x+2-x+1/x2+2x

1 Answer

1 vote

Question

x+5/x+2 - x+1/x²+2x

Answer:

= (x² - 4x - 1)/[x (x+2)]

= (x² - 4x - 1)/[x² + 2x]

Explanation:

x + 5/x + 2 - x + 1/x² + 2x

We factorise the second denominator to give us :

x + 5/x + 2 - x + 1/x(x + 2)

We find the L.C.M of both denominators which is x(x+2).

[x(x + 5)-(x + 1)] / (x (x + 2))

Expand the bracket

=[x² +5x - x -1] / [x (x + 2)]

=(x² - 4x - 1) / [x (x + 2)]

= (x² - 4x - 1)/ [x (x + 2)]

= (x² - 4x - 1) / [x² + 2x]

User BeeZee
by
6.1k points